IFC The First Six Decades : Leading the Way in Private Sector Development--A History - International Finance Corporation (International Finance Corporation, Washington, DC, 2016)
This is a story of experience - an unparalleled body of knowledge built up in the toughest markets, under the most challenging conditions, and applied to address the world’s most urgent development challenges. Six decades ago, a few dozen countries made a calculated bet on the transformative potential of the private sector in developing countries. They put up 100 million dollars in capital and established International Finance Corporation (IFC) to reinforce the work of the World Bank in spurring growth and development. Today, IFC is the largest global development institution focused on the private sector, having delivered nearly 250 billion dollars in financing to businesses in emerging markets. Throughout its history, IFC has introduced new approaches to meet the needs of developing countries. IFC consistently brought to bear a distinctive set of advantages in working with the private sector to end extreme poverty and boost shared prosperity - a history of innovation, a mandate for global influence, an understanding of the demonstration effect of its actions, and a determination to achieve measurable development impact. Six decades of experience and a record of innovation and thought leadership in private sector development have made the organization essential for creating opportunity where it’s needed most.